IMPLEMENTASI KEBIJAKAN PADA PENDISTRIBUSIAN PROGRAM KELUARGA HARAPAN UNTUK PEMBERDAYAAN MASYARAKAT MISKIN DI KELURAHAN DUAMPANUA KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Aliza, Nur; Irwan; Rusdi, Muhammad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to find out how the policy is implemented in the distribution of the family hope program for the empowerment of poor communities in Duampanua Subdistrict, Baranti Subdistrict, Sidenreng Rappang Regency. The research method used is descriptive qualitative. Data was obtained by conducting more in-depth observations and interviews with the sub-district head, social assistance assistants, and beneficiary families. Then the data obtained from the interview results was processed using the Nvivo 12 Plus application. The research results show that the implementation of policies in the distribution of the Hope Family program has been realized, but in terms of target accuracy, this program is considered to be less effective. The factors that hinder the distribution of this program are external factors and internal factors.